2021
DOI: 10.3390/ijerph18084074
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Residents’ Purchase Intention of Green Housings in China: An Extended Perspective of Perceived Value

Abstract: The promotion of green housings (GHs) is considered a potentially effective way to save energy, reduce air pollution, and promote industrial upgrading. However, the low level of public acceptance of GHs leads to insufficient GH market penetration in China. Thus, it is significant to explore GH purchase decisions to understand and enhance the market demand for GHs effectively. From an extended perspective of perceived value, this study proposes a comprehensive research model that integrates residents’ perceptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 87 publications
(158 reference statements)
0
24
0
1
Order By: Relevance
“…Egoistic and ecological values showed partial mediation between perceived benefits and willingness to pay for both framing contexts. Zhao and Chen (2021) found that perceived value is a crucial predictor of green housing purchase intention. Huang (2014) used the structural equation model to systematically study the willingness of consumers to pay for green housing, and through questionnaire surveys, it was found that factors such as consumer economy, social status, consumer expectations, consumer perception, external stimuli, and other factors have significant impacts on willingness to pay.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Egoistic and ecological values showed partial mediation between perceived benefits and willingness to pay for both framing contexts. Zhao and Chen (2021) found that perceived value is a crucial predictor of green housing purchase intention. Huang (2014) used the structural equation model to systematically study the willingness of consumers to pay for green housing, and through questionnaire surveys, it was found that factors such as consumer economy, social status, consumer expectations, consumer perception, external stimuli, and other factors have significant impacts on willingness to pay.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Los consumidores que compraron estas viviendas fueron reconocidos y aceptados socialmente, dándole una imagen positiva a sus personas. Por lo tanto, se puede afirmar que el beneficio social tiene una relación positiva con la intención de compra (Gan y Wang, 2017;Liu, 2021;Vijaranakorn y Shannon, 2017;Zhao y Chen, 2021).…”
Section: Beneficio Socialunclassified
“…Environmental concerns may be defined as the extent to which individual are aware of environmental challenges and exert efforts to find solutions ( Jiang and Kim, 2015 ). According to Zhao and Chen (2021) research on the green housing setting, consumers with higher environmental concerns would focus on environmental performance of a product. As a result, his concern rises for environmental acts, such as green buying intentions ( Bouscasse et al, 2018 ).…”
Section: Generativity Attitude Toward Organic Food and Dining Intentionmentioning
confidence: 99%